APPLICATION OF THE HEALTH BELIEF MODEL IN NUTRITION EDUCATION TO IMPROVE HEMOGLOBIN LEVELS OF PREGNANT WOMEN: A SYSTEMATIC REVIEW AND META-ANALYSIS - Yusnia Nur Aziizah; Choirul Anna Nur Afifah; Maulidah Ayunintyas; Fatimah Nur Fadilah; Trias Mahmudiono; Dini Ririn Andreas; Sigit Ari Saputro (Journal of Nutrition College, 2026)
ABSTRACTBackground: Anemia is a common complication during pregnancy and poses a global public health risk and a threat to both maternal and infant health. Nutrition education interventions influenced by the Health Belief Model (HBM) have been able to improve health behaviors and increase hemoglobin levels.Objective: This systematic review and meta-analysis aims to determine if HBM-based nutrition education interventions are effective in increasing hemoglobin levels in pregnant women.Methods: Randomized controlled trials that HBM nutrition education interventions and hemoglobin levels in pregnant women were located in the literature and reviewed. Five out of the determined studies were selected. We conducted a meta-analysis to determine the mean difference in hemoglobin levels of the intervention and control groups.Results: All studies included showed HBM-based interventions is a statistically significant increase in hemoglobin levels in women. The mean difference is an increase of 1.35 g/dL (95% CI: 0.52 to 2.17) which is an increase of a clinically significant number. High levels of heterogeneity were noted based on the differences in participant characteristics, and the intervention's duration and intensity. There was no significant evidence of publication bias.Conclusions: Based on the Health Belief Model, nutrition education interventions positively impact the increase of pregnant women’s hemoglobin levels. This model has helped improve the adherence of women to iron supplements and dietary changes, which decreases the severity of anemia during pregnancy. There is a need for future studies to focus on the specific components of the interventions to determine the effects on long-term outcomes to enable the studies to be used in various situations.Keywords: Health belief model; nutrition education; anemia; hemoglobin; pregnancy; systematic review; meta-analysis